PENGARUH CORPORATE GOVERNANCE TERHADAP ENVIRONMENTAL STRENGTH DALAM CORPORATE SOCIAL RESPONSIBILITY - Windijarto Windijarto; Sekar Ajeng Savitasari (Politeknik Negeri Lhokseumawe, 2020)
Abstract : This study aims to analyze the relationship between corporate governance (board independence dan board size) to the implementation of environmental standards in corporate social responsibility. This study uses a sample of 200 manufacturing companies listed on the Indonesia Stock Exchange (IDX) taken from 2015-2016. The result of this research is that there is a significant and positive influence between board independence and board size of commissioners on the environmental strength in corporate social responsibility. Keywords: corporate governance, board independence, board size, environmental strength, corporate social responsibility